Engineering Polyzwitterion and Polydopamine Decorated Doxorubicin-Loaded Mesoporous Silica Nanoparticles as a pH-Sensitive Drug Delivery - Ji, Feng (Polymers (Basel), 2018)
Multifunctional drug carriers have great applications in biomedical field. In this study, we introduced both polydopamine (PDA) and zwitterionic polymer of poly(3-(3-methacrylamidopropyl-(dimethyl)-ammonio)propane-1-sulfonate) (PSPP) onto the surface of mesoporous silica nanoparticles (MSNs) to develop a novel nanoparticle (MSNs@PDA-PSPP), which was employed as a new kind of drug carrier for the delivery of doxorubicin (DOX). The PDA coating, as a gatekeeper, could endow the drug carrier with pH-sensitive drug release performance. The outermost PSPP layer would make the drug carrier possess protein resistance performance. The chemical structure and properties were characterized by Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), dynamic light scattering (DLS) and thermogravimetric analysis (TGA). MSNs@PDA-PSPP could keep good colloidal stability within 72 h in phosphate buffered saline (PBS) and protein solutions. Meanwhile, MSNs@PDA-PSPP exhibited a high drug loading for DOX. In vitro drug release experiments suggested MSNs-DOX@PDA-PSPP exhibited pH-dependent drug release behaviors. Besides, MSNs@PDA-PSPP had no cytotoxicity to human hepatocellular carcinoma cells (HepG2 cells) even at a concentration of 125 µg/mL. More importantly, cellular uptake and in vitro anticancer activity tests suggested that MSNs-DOX@PDA-PSPP could be taken up by HepG2 cells and DOX could be successfully released and delivered into the cell nuclei. Taken together, MSNs@PDA-PSPP have great potential in the biomedical field.